Training and Assistance in the Use of DJP Applications to Motivate Khairul Imam IT High School Teachers in Preparing Financial Statements and Online Tax Reporting - Dhita Adriani Rangkuti; Dwita Sakuntala; Jholant B. L Amelia Br. Sinaga; Yeni Rafita Sihombing; Mila Yulia Herosian; Khomeiny Yunior (RECORD: Journal of Loyality and Community Development, 2024)
The benefits of technology are also increasingly sophisticated and make it easier for educators to carry out all tasks such as using a computer or laptop in preparing reports and learning using visual media, preparing annual reports such as tax payments can also be done online using the online DGT application. Motivation itself is a change in energy within (personal) a person which is indicated by the appearance of feelings and reactions to achieve goals. This training was held to motivate Khairul Imam IT High School teachers to prepare financial and online tax reports. This activity was carried out in June 2024, with as many as 20 people participating in the activity and 6 lecturers who also acted as resource persons.